Changes for Samantha : a winter story - Tripp, Valerie, 1951- (American girls collection., 1988)
When she discovers that Nellie and her sisters have been sent to an orphanage, Samantha, now living with her aunt and uncle in New York City, tries to help her friends as much as she can.